The Degree of Student _ Teachers' Practice the Cooperative Learning Principles during the Execution of Practical Education Lessons: “A Field Study at the Faculty of Education, Tishreen University” (Journal of Hama University, 2025)
The research aimed to determine the degree of student _ teachers' practice the cooperative learning principles during the execution of practical education lessons.The two researchers used a descriptive approach and prepared an observation card. The search sample included (155) student _ teachers. The research results showed that:The student _ teachers practice the cooperative learning principles during the execution of practical education lessons to a medium degree, and that the work of one of the parents at least in the teaching profession raises the degree of the student _ teachers' practice the cooperative learning principles, as well as following a course in the field of preparing teachers raises the degree of the student _ teachers' practice the cooperative learning principles, and in light of the research results, the two researchers presented some recommendations.
Keywords: Degree of Practice; Student _ Teachers; Principles of Cooperative Learning; Practical Education